PRACTICAL USE OF VIBRATION DIAGNOSTICS METHODS FOR DETERMINATION OF ROLLING STOCK INTEGRATED PARAMETERS - Alexander B. Suvorov; Tatiana V. Suvorova; Sergey A. Usoshin (Advanced Engineering Research, 2011)
The procedure of one of the vibration diagnostics problems is described: determination of the integrated parameters of the moving train (time of passing the railway checkpoint, rail number, type of locomotive, type of cars, speed of the rolling stock, number of cars).